2003
DOI: 10.1159/000075697
|View full text |Cite
|
Sign up to set email alerts
|

Esomeprazole 40 mg Provides Improved Intragastric Acid Control as Compared with Lansoprazole 30 mg and Rabeprazole 20 mg in Healthy Volunteers

Abstract: Aim: To compare the effects of standard-dose esomeprazole with those of standard doses of lansoprazole and rabeprazole on intragastric pH during repeated daily oral dosing in healthy volunteers. Methods: In two standardized, randomized crossover studies, Helicobacter pylori negative healthy volunteers (study A: 19 males, 5 females; study B: 13 males, 10 females) received esomeprazole 40 mg and either lansoprazole 30 mg (study A) or rabeprazole 20 mg (study B) orally once daily in the morning for 5 days. Contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 17 publications
5
26
0
2
Order By: Relevance
“…However, rabeprazole at 20 mg increased intragastric pH compared with esomeprazole at 20 mg on Day 1 and showed a higher AUC and intragastric pH on Day 118 while also producing greater acid suppression on Day 1 than esomeprazole at 40 mg, particularly at night 19. Findings from these studies suggest that rabeprazole has a faster onset of acid inhibitory action than esomeprazole at either 20 or 40 mg from Day 1,19 although esomeprazole remains the most effective PPI from Day 5 20. Physicians should therefore consider the time and onset of treatment when selecting a PPI.…”
Section: Characteristics Of Esomeprazolementioning
confidence: 84%
“…However, rabeprazole at 20 mg increased intragastric pH compared with esomeprazole at 20 mg on Day 1 and showed a higher AUC and intragastric pH on Day 118 while also producing greater acid suppression on Day 1 than esomeprazole at 40 mg, particularly at night 19. Findings from these studies suggest that rabeprazole has a faster onset of acid inhibitory action than esomeprazole at either 20 or 40 mg from Day 1,19 although esomeprazole remains the most effective PPI from Day 5 20. Physicians should therefore consider the time and onset of treatment when selecting a PPI.…”
Section: Characteristics Of Esomeprazolementioning
confidence: 84%
“…While some studies have documented genotype dependent differences in acid suppression and outcomes, others showed no relation between genotype and degree of acid suppression or outcomes for rabeprazole and esomeprazole [40,48,53,71,73,108]. This may be attributed in part to their lesser dependence on CYP2C19 metabolism, the higher potency of these PPIs [53,109,110], compared to other PPIs, lack of *17 testing [71], or combination of these factors, leading to diminished differences between the different CYP2C19 metabolizer phenotypes. Although the CYP2C19 genotype dependent increase of AUC in patients with PM phenotype may be less for PPIs that are minimally metabolized by CYP2C19, such as rabeprazole, the elevation in drug concentrations may still pose a risk of adverse events given its high potency.…”
Section: Expert Opinionsmentioning
confidence: 99%
“…Previous studies have demonstrated that intragastric acid is more effectively controlled with esomeprazole than rabeprazole, omeprazole, lansoprazole and pantoprazole, as measured by the percentage of time pH > 4.0 and mean 24-hour pH. [14][15][16][17] In a five-way crossover study, standard-dose esomeprazole also was shown to provide a greater mean number of hours in a 24-hour period with pH above prespecified thresholds (between 2.0 and 6.0) than standard doses of rabeprazole, omeprazole, lansoprazole and pantoprazole. 17 These results are consistent with those of previous studies comparing standard and escalated doses of esomeprazole, either alone or in comparison with other PPIs.…”
Section: Mean 24-hour Phmentioning
confidence: 99%
“…[11][12][13] Intragastric acid is more effectively controlled with the standard dose of esomeprazole (40 mg once daily) than standard doses of all other PPIs, as measured by the percentage of time pH > 4.0 and mean 24-hour pH. [14][15][16][17] Furthermore, esomeprazole provides complete heartburn relief in the majority of patients with GERD.…”
Section: Introductionmentioning
confidence: 99%